Fifty things that aren't my fault : essays from the grown-up years - Guisewite, Cathy (Waterville, Maine : Thorndike Press, a part of Gale, a Cengage Company, 2019)
As the creator of the comic strip "Cathy," Cathy Guisewite returns with her signature wit and warmth in this debut essay collection about another time of big transition, when everything starts changing and disappearing without permission: aging parents, aging children, aging self stuck in the middle. Guisewite unearths the humor and horror of everything from the mundane (trying to introduce her parents to TiVo and facing four decades' worth of unorganized photos) to the profound (finding a purpose post-retirement and declaring freedom from all those things that hold us back).
Fifty things that aren't my fault -- Why there's a lifeless body in dressing room number two -- Driving lessons -- In loving memory of the legs l used to hate -- The attack mom -- The day I outgrew all my shoes -- I would wash my hands of this if only I could -- Caregiver standoff at the ice cream parlor -- Cords -- At least I didn't eat a donut -- The build-a-boob workshop -- Infidelity -- Nobody wants to hear about your nice clean closet -- No comment -- Helicopter daughter -- Diary of a bubble wrap scrap -- I'm flunking retirement -- This is your brain on sweet potato chips -- Don't tell a woman to just wear jeans -- The organizer -- Love stories -- The day I washed my face with bath soap -- It took a village -- The itsy-bitsy, teeny-weeny torture chamber -- The day I divorced my purse -- Stop trying to upgrade your mother -- Ode to eyeliner -- What kind of friend has no Wi-Fi in the powder room? -- In defense of my 2,000th trip to the mall -- My meaningless midlife six-minute fling -- Four kindergarten moms and a bottle of Pinot Grigio -- Joyfully preparing for the celebration of death -- Left at the altar -- Seduction 101 -- The last champions of photo album guilt -- Prince Charming -- Unexpired love -- Ate o'clock -- Mother's Day text message -- Novocaine in the waiting room -- Cool whipped -- Never, ever do what I say -- Love is in the air -- Barbie mom -- Meditations on a sweat sock -- Mother's soup -- Superman versus the meatloaf -- My cup would runneth over except it was full of M&M's and now they're all gone.
107691
Keywords: Guisewite, Cathy -- Family -- Humor; Families -- Humor; Cartoonists -- Biography; Essays; Autobiographies; Large type books; Humor